2016
DOI: 10.1111/edt.12286
|View full text |Cite
|
Sign up to set email alerts
|

Study of the causes of facial fractures in a reference center in Rio de Janeiro, Brazil from 2003–2012

Abstract: In the city of Rio de Janeiro, young men in their fourth decade of life are prone to trauma to their facial bones, especially the mandible, and they are most commonly caused by traffic accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 18 publications
(29 reference statements)
2
20
0
Order By: Relevance
“…In a study published by Farneze et al ( 22 ) in 2016 that described maxilomandibular trauma of patients at a reference center in oral and maxillofacial service, the mean age was 33.7 years old, with men accounting for 81% of the cases. The main etiology was injuries related to traffic accidents (47%), especially motorcycle accidents.…”
Section: Discussionmentioning
confidence: 99%
“…In a study published by Farneze et al ( 22 ) in 2016 that described maxilomandibular trauma of patients at a reference center in oral and maxillofacial service, the mean age was 33.7 years old, with men accounting for 81% of the cases. The main etiology was injuries related to traffic accidents (47%), especially motorcycle accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that 81% of maxillofacial traumas were observed among men. 20 Based on the results of other studies, men were more prone to traumatic injuries probably due to dealing more with physical activities and disputes. 5,13,21 Regarding the reason for traumas, approximately twothird of cases were allotted to driving accidents with vehicles, and falling from a height, disputes and injuries with a warm gun, along with sports and occupational accidents, were the other causes of maxillofacial traumas in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, a number of similar studies reported the same age distribution for maxillofacial traumas. [19][20][21]23 However, in a study done in the United Arab Emirates, the second decade of life was reported as the most prevalent age group of maxillofacial traumas, which is attributed to further use of motorcycles by young people. 24 In the present study, nearly one-third of cases had mandibular fractures in their history.…”
Section: Discussionmentioning
confidence: 99%
“…Maxillofacial trauma (MFT) is particularly important because it is responsible for a large fraction of emergency visits and the morbidity and mortality in trauma centers, which is reflected in a lack of hospital and polyclinic beds, in addition to the costs associated with the treatment, recovery and rehabilitation of these patients ( 1 - 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that traffic accidents and falls are the most prevalent etiologies of MFT ( 5 - 9 ). These etiologies represent real challenges both for the management of public policies targeting the care of this population through the implementation of primary care programs focused on the prevention of the main etiological factors and the factors associated with MFT and for the care professionals involved in the treatment of increasingly severe injuries ( 1 , 5 , 6 , 7 , 9 - 11 ).…”
Section: Introductionmentioning
confidence: 99%